An evaluation of short-acting β2-agonist prescriptions and associated clinical outcomes in asthma management in Indonesia – the SABINA Indonesia study - Wiwien Heru Wiyono; Muhammad Amin; Susanthy Djajalaksana; Amira Permatasari Tarigan; Febrina Susanti; Hisham Farouk; Helyanna Helyanna (Jurnal Respirologi Indonesia, 2022)
Background: Asthma is a chronic inflammatory disease, therefore inhaled corticosteroid (ICS) should be as the cornerstone of asthma treatment. However patients tend to rely on short-acting β2-agonist (SABA) due to immediate symptom relief and underuse ICS, thereby undertreating the underlying inflammation. As part of the multi-country SABA use IN Asthma (SABINA) III study, we aimed to describe SABA prescription patterns and asthma-related clinical outcome in Indonesia.Methods: Cross-sectional study in asthma patients (> 12 years old) during August 2019 –  January 2020. Disease characteristic, prescribed asthma treatment in the 12 months before the study visit, and clinical outcomes, were recorded during a single visit and entered into an electronic case report form.Results: Of 219 patients recruited, the mean number of SABA canisters prescribed was 4 canisters per year. SABA over-prescription (≥ 3 canisters/year) seen in 37% patients, and was greater in moderate-to-severe vs mild asthma (40% vs 17.9%). 47.5% of patients had at least 1 severe exacerbation; and 7.3% of patients had ≥3 severe exacerbations, in the past 12 months. Almost half of the patients (40.2%) were prescribed oral corticosteroids (OCS). Overall, the well-, partly, and uncontrolled patients were 41.6%, 37.4%, and 21%, respectively.Conclusion: SABA over-prescription occurs in approximately one third of asthma patients, especially among moderate-to-severe patients and almost half of asthma patients experienced at least 1 severe exacerbation in the previous year. This highlights a public health concern and the need to improve asthma care by aligning with global recommendations including reducing SABA over-reliance in Indonesia